Phylogeny and systematics of Arabian lacertids from the Mesalina guttulata species complex (Squamata, Lacertidae), with the description of a new species - Jiří Šmíd; Doubravka Velenská; Lukáš Pola; Karin Tamar; Salem Busais; Mohammed Shobrak; Mohammed Almutairi; Al Faqih Ali Salim; Saad Dasman Alsubaie; Raed Hamoud M. AlGethami; Abdulaziz Raqi AlGethami; Abdulkarim Saleh K Alanazi; et al. (BMC Zoology)
Abstract Background The lacertid genus Mesalina has been the subject of several phylogenetic and biogeographic studies as well as taxonomic revisions within the last decade. The genus is partitioned into seven main clades, some of which represent species complexes of morphologically very similar species. The Mesalina guttulata species complex is one such case. This complex currently comprises four described species that occur through Arabia and northern Africa, however, the presence of a cryptic species in Saudi Arabia, Kuwait, and Jordan was pointed out recently. For this study, we collected new material of the various species of the M. guttulata complex, including the undescribed lineage from across Saudi Arabia. We carried out multilocus phylogenetic analyses using three mitochondrial and three nuclear markers and analysis of morphological data to verify whether the undescribed lineage deserves a species rank. Results The results show that the lineage is clearly genetically separated from the other species of the complex and shows morphological differentiation from the other species. Therefore, we describe it herein as a new species, Mesalina cryptica sp. nov. Conclusions We contribute to the taxonomy of Arabian lacertid lizards by describing a new species distributed in central Saudi Arabia, with isolated populations occurring in Kuwait and Jordan. Despite its large range, the species is genetically and morphologically homogeneous. The gap in its distribution between the Jordan and Saudi Arabia populations is ascribable to the paucity of sampling along the Saudi/Iraqi border.